2006
DOI: 10.1016/j.heares.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Deafness associated changes in expression of two-pore domain potassium channels in the rat cochlear nucleus

Abstract: Two-pore domain potassium channels ( ) play an important role in setting resting membrane potential by regulating background leakage of potassium ions, which in turn controls neuronal excitability. To determine whether these channels contribute to activity-dependent plasticity following deafness, we used quantitative real-time PCR to examine the expression of 10 subunits in the rat cochlear nucleus at 3 days, 3 weeks and 3 months after bilateral cochlear ablation. There was a large sustained decrease in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 54 publications
3
29
2
Order By: Relevance
“…Previous RT-PCR and in situ hybridization studies have revealed that TWIK-1 is present in the mammalian brain and also in a wide variety of tissues outside the nervous system (Lesage et al, 1996;Orias et al, 1997, Arrighi et al, 1998 Wang et al,1998;Medhurst et al, 2001 andTalley et al, 2001). TWIK-1 expression has been previously shown in the cochlear nucleus using PCR (Holt et al, 2006) and in the inner ear and cochlear nucleus using in situ hybridization (Nicolas MT et al, 2003;Talley et al, 2001). In the present study, a decrease in TWIK-1 expression was found which did not reach significance until 3 weeks following deafening (24% decrease, p=0.003) and remained significantly decreased by 20% (p=0.002) at 3 months following deafness (Figure 2A).…”
Section: Pcr Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Previous RT-PCR and in situ hybridization studies have revealed that TWIK-1 is present in the mammalian brain and also in a wide variety of tissues outside the nervous system (Lesage et al, 1996;Orias et al, 1997, Arrighi et al, 1998 Wang et al,1998;Medhurst et al, 2001 andTalley et al, 2001). TWIK-1 expression has been previously shown in the cochlear nucleus using PCR (Holt et al, 2006) and in the inner ear and cochlear nucleus using in situ hybridization (Nicolas MT et al, 2003;Talley et al, 2001). In the present study, a decrease in TWIK-1 expression was found which did not reach significance until 3 weeks following deafening (24% decrease, p=0.003) and remained significantly decreased by 20% (p=0.002) at 3 months following deafness (Figure 2A).…”
Section: Pcr Resultssupporting
confidence: 54%
“…These subunits were also shown to be expressed in the rat cochlear nucleus with PCR (Holt et al, 2006) and TREK-1 immunostaining was shown in the rat cochlea (Kanjhan et al, 2004a) and cochlear nucleus (Kanjhan et al, 2004b). In the current study all three subunits are expressed in the IC ( Figure 2B).…”
Section: Pcr Resultsmentioning
confidence: 90%
See 3 more Smart Citations